Allometric models for Bauhinia monandra Kurz leaf area determination - Schmildt, Edilson Romais; Schmildt, Omar; Alexandre, Rodrigo Sobreira; Fernandes, Adriano Alves; Czepak, Marcio Paulo (Comunicata Scientiae, 2016)
The aim of this study was to evaluate the efficiency of the adjustment of mathematical models for determining Bauhinia monandra leaf area using the length and/or width of the leaves as independent variables. Leaves from plants with three years were used to the estimative of equations in linear, quadratic and potential models. The validation from the estimated leaf area as a function of the observed leaf area showed that the linear model based on the product of length and width of the largest leaf surface is the model that best fits. However, the leaf area determination can be represented by using only the length or width of the leaves with little loss of accuracy. A representation that better estimates Bauhinia monandra leaf area with easy application is the potential model in which xi represents the length of one of the symmetrical leaf lobes.